Group lending with peer selection and moral hazard - Hernandez, Manuel A.; Liu, Yanyan; Gan, Li (Scientific Research Publishing, Inc., 2022)
The theory on group lending suggests that joint liability induces borrowers to form homogeneous groups based on their risk types, which alleviates adverse selection and contributes to the success of microcredit schemes. We extend this theory by allowing individuals to differ both in their exogenous risk type and in their endogenous effort level. We find that joint liability leads to positive assortative matching in both a non-cooperative and cooperative game setting. Groups of safe borrowers additionally exhibit higher effort levels, which reinforces their likelihood of repayment as opposed to risky groups.